Adaptation of Melodic Intonation Therapy to Greek: A Clinical Study in Broca’s Aphasia With Brain Perfusion SPECT Validation - Martzoukou, Maria; Nousia, Anastasia; Nasios, Grigorios; Tsiouris, Spyridon (Frontiers in Aging Neuroscience, 2021)
Melodic intonation therapy (MIT) is one of the most well-known treatment methods which is based on pitch and rhythm and was developed to increase verbal output in adults with non-fluent aphasia. Although MIT has been adapted to several languages, in Greece it is almost unknown. The aim of the proposed study is twofold: (1) to translate and adapt the MIT to the Greek language, and (2) to conduct an experimental study in order to examine the effect of MIT on Greek patients with Broca’s aphasia. To this aim, a 64-year-old, right-handed male who had a 6-year primary school education level, no musical abilities and poor performance on the recognition of prosody attended the MIT intervention program almost two and a half years after the event of suffering an ischemic stroke. The MIT intervention was administered three times per week for a 12-week period, in which each session lasted from 30 to 40 min. The patient underwent three assessments all using both the Boston Diagnostic Aphasia Examination–Short Form (BDAE-SF) and brain perfusion single-photon emission computed tomography (SPECT); (1) before the MIT, (2) immediately after, and (3) 3 months after the completion of MIT. The results from the BDAE-SF revealed an impressive improvement on both trained and prepositional speech production, immediately after the completion of the MIT, and a stable improved performance 3 months after MIT. The SPECT scan revealed reactivation of the perilesional areas of the left hemisphere, and considerably improved perfusion of the frontal lobe, the anterior temporal lobe, and the upper part of the parietal lobe of the right hemisphere. The improvement persisted and even expanded 3 months after MIT. Therefore, MIT is a promising intervention program and its positive effects last for at least 3 months after the completion of the intervention.